Modeling of graphene nanoribbon field effect transistor - Rahmani, Meisam (2013)
The scaling of Field Effect Transistor (FET) at nanoscale assures better performance of the device. The phenomenon of downsizing the device dimensions has led to challenges such as short channel effects, leakage current, interconnect difficulties, high power consumption and quantum effects. Therefore, new materials and device structures are needed as alternatives to overcome these challenges. In this research, an analytical model for Trilayer (ABA-stacked) Graphene Nanoribbon carrier statistics based on quantum confinement effect is presented. To this end, density of states, carrier concentration and ballistic conductance of Trilayer Graphene Nanoribbon (TGN) as an FET channel are modeled. Besides that, scaling behaviors of p-n junction, Homo junction, Schottky-barrier diode and Schottkybarrier FET based on the Graphene Nanoribbon application are analytically studied. This is demonstrated in the proposed structure of TGN Schottky-barrier FET that exhibits negligible short channel effects, improved on current, pragmatic threshold voltage, very good subthreshold slope, and fast transient between on-off states to meet the International Technology Roadmap for Semiconductors (ITRS) near-term guidelines. Therefore, the proposed model is suitable for a high speed switching application because the value of subthreshold slope for the proposed transistor is less than the ideal value of 60 mV/decade. A small value of subthreshold slope denotes a small change in the input bias which can modulate the output current and would lead to less power consumption. Finally, an analytical modeling of Graphene-based NO2 gas sensor is proposed. MATLAB software was used to implement the numerical methods for modeling and data analysis. Observations of the presented models showed acceptable agreement with the published data.